El Turismo como Objeto de Investigación -Tourism as an Object of Study - Gil, Sergio Moreno; Korstanje, Maximiliano E. (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2020)
RESUMEN A pesar de la producción bibliográfica de las últimas décadas, los investigadores asisten a una gran fragmentación en los sentidos que cada disciplina le asigna al Turismo. El paradigma de la sustentabilidad económica ha regido la producción de los estudios turísticos por años, no obstante, en la actualidad la epistemología parece haber entrado en crisis. El presente trabajo discute e intenta una definición de Turismo a través de su objeto de estudio. En cierta forma, el progreso de la investigación sobre Hospitalidad y Turismo dependerá de la capacidad de los académicos y profesionales de desarrollar una teoría rigurosa basada en la investigación que permita conceptualizar de forma práctica y teórica el término en forma integrada. PALABRAS CLAVES Turismo. Hospitalidad. Epistemología. Objeto de Investigación. Definición. ABSTRACT Despite of the over production of the Tourism-related scholars over the recent decades, there is still a great fragmentation in the sense of tourism, as well as the interpretation of each discipline about Tourism. Though the paradigm of sustainability has ruled the discipline for years, no less true is that in the recent years the object of study of Tourism has waded into crisis. The present text attempts a shared definition of tourism through its object of study. Certainly, the progress of tourism investigation depends on the capacity of scholarship and policy makers to shape an exhaustive definition towards a more integrated form. KEY WORDS Tourism. Hospitality Epistemology. Object of Study. Definition. AUTORIA Sergio Moreno Gil – Doutor. Universidad de la Palma de la Gran Canaria, España. Currículo: https://www.researchgate.net/profile/Sergio_Moreno-Gil/3 E-mail: sergio.moreno@ulpgc.es Maximiliano E. Korstanje – Licenciado. Professor na Universidad de Palermo, Buenos Aires, Argentina. Currículo: https://palermo.academia.edu/MaximilianoEKorstanje/CurriculumVitae E-mail: mkorst@palermo.edu Patricia Picaso Peral – Doutora. Universidad de la Palma de la Gran Canaria, España. Curriculo: https://www.linkedin.com/in/patriciapicazo/?originalSubdomain=es. Email: patricia.picazo@ulpgc.es BIBLIOGRAFÍA Airey, D. & Tribe, J. (2000). Education for hospitality. In C. Lashley C. & A. Morrison (Eds). Search of Hospitality: Theoretical Perspectives and Debates. (pp. 192-276). Oxford: Butterworth-Heinemann. Andersson, T. & Getz, D. (2009). Tourism as a mixed industry: differences between private, public and not-for-profit festivals. Tourism Management, 30(6), 847–856. Link Ashworth, G. J. & Voogd, H. (1990). Selling the city: marketing approaches in public sector urban planning. London: Belhaven Press. Ashworth, G. J. & Goodall, B. (Eds). (1995). Marketing in tourism industry: the promotion of destination regions. London: Thomson Publishing. Baggio, R. (2008). Symptoms of complexity in a tourism system. Tourism Analysis, 13(1), 1-20. Link Baloglu, S. & Assante, L.M. (1999). A content analysis of subject areas and research methods used in five hospitality management journals. Journal of Hospitality & Tourism Research, 23(1), 53-70. Link Balaguer, J. & Cantavella-Jorda, M. (2002). Tourism as a long-run economic growth factor: the Spanish case. Applied Economics, 34(7), 877-884. Link Bell, D. (2007). The hospitable city: social relations in commercial spaces. Progress in Human Geography, 31(1), 7-22. Link Bertalanffy, L. (1968). General Systems Theory. New York: Brazillier. Bigné Alcañiz, E., Pont Aulet, X. & Andreu Simó, L. (2000). Marketing de Destinos Turísticos. Análisis y Estrategias de Desarrollo. Madrid: Esic. Bigné, J. E., Aldás, J., Küster, I. & Vila, N. (2002). Estableciendo los determinantes de la fidelidad del cliente: Un estudio basado en técnicas cualitativas. Investigación y Marketing, 77, 58-62. Brotherton, B. (1999). Towards a definitive view of the nature of hospitality and hospitality management. International Journal of Contemporary Hospitality Management, 11(4), 165-173. Link Brotherton, B. (2003). The international hospitality industry structure, characteristics and issues. Oxford: Elsevier Butterworth-Heinemann. Bull, A. (1994). La Economía del sector turístico. Madrid: Alianza Editorial. Calantone, R.J. & Mazanec, J.A. (1991). Marketing management and tourism. Annals of Tourism Research, 18(1), 101-119. Link Camisón Z.C. & Monfort, M.V. (1998). Estrategias de reposicionamiento para destinos turísticos maduros: el caso de la Costa Blanca. Estudios Turísticos, 135, 7-28. Link Chambers, D., & Rakić, T. (2015). Tourism research frontiers: an introduction. In Tourism research frontiers: Beyond the boundaries of knowledge (pp. 1-11). Bingley, Reino Unido: Emerald. Cooper, C, Fletcher, J., Gilbert, D., Shepherd, R. & Wanhill, S. (1998). Tourism: Principies and Practice. Longman, Harlow. Chen, K.C. & Groves, D. (1999). The importance of examining philosophical relationships between tourism and hospitality curricula. International Journal of Contemporary Hospitality Management, 11(1), 37-42. Link Choy, D.J.L. (1992). Alternative roles of national tourism organizations. Tourism Management, 14(5), 357-365. Link Davidson, R. & Maitland, R. (1997). Tourism destinations. Reino Unido: Hodder y Stoughton. Enloe, C. (1989). Bananas, beaches and bases. Making feminist sense of international politics. London: Pandora. European Commission. (2000). Towards quality coastal tourism. Integrated Quality Management (IQM) of coastal tourist destinations. Brussels: European Commission. Enterprise Directorate-General. Tourism Unit. Farrell B. H., & Twinning-Ward L. (2004). Reconceptualizing tourism. Annals of Tourism Research, 31(2), 274-295. Link Frechtling, D. C. (2004). Assessment of tourism/hospitality journals' role in knowledge transfer: an exploratory study. Journal of Travel Research, 43(2), 100-107. Link Ghali, M. A. (1976). Tourism and economic growth: an empirical study. Economic Development and Cultural Change, 24(3), 527-538. Gleick, J. (1987). Chaos. London: Sphere Books. Graburn, N.H.H. & Jafari, J. (1991). Tourism social science. Annals of Tourism Research, 18, 1-11. Gunn, C. (1988). Vacationscape: designing tourist regions. New York: Van Nostrand Reinhold. Haan, T., Ashworth, O. & Stabler, M. (1991). The tourist destination as a product: the case of Languedoc. En Asworth & Goodall. Marketing tourism places. (pp. 180-193). Londres: Routledge. HALL, C.M. (2000). Tourism planning: Policies, processes, relationships. New Jersey: Prentice-Hall. Hemmington, N. (2007). From service to experience: understanding and defining the hospitality business. The Service Industries Journal, 27(6), 747-755 Link Hepple, J., Kipps, M. & Thomson, J. (1990). The concept of hospitality and an evaluation of its applicability to the experience of hospital patients. International Journal of Hospitality Management, 9(4), 305-317. Link Holden, A. (2004). Tourism studies and the social sciences. Abingdon: Routledge. Howey, R.M., Savage, K.S., Verbeeten, M.J. & Van Hoof, H.B. (1999). Tourism and hospitality research journals: cross-citations among research communities. Tourism Management, 20(1), 133-139. Link Ingram, H. (1996). Clusters and gaps in hospitality and tourism academic research. International Journal of Contemporary Hospitality Management, 8(7), 91-95. Link Innerarity, D. (2001). Ética de la hospitalidad. Barcelona: Península. Jafari, J. (1989). Structure of tourism. En S.F. Witt & L. Moutinho. Tourism marketing and management handbook. (pp. 500-656) London: Prentice Hall. Jafari J. (1993). Anchoring tourism projects on a scientific foundation. In The First International Conference on Investments and Financing in the Tourism Industry conference proceedings. Jerusalem: Israel Ministry of Tourism. <a href="https://scholar.google.com/scholar?hl=es&as_sdt=0%2C5&q=+++++Jafari+J.+%281993%29.+Anchoring+tourism+projects+on+a+scientific+foundation.+In+The+First+International+Conference+on+Investments+and+Financing+in+the+Tourism+Industry+conference+proceedings.+Jerusalem%3A+Israel+Ministry+of+Tourism&btnG=">Link Jamal, T., Smith, B. & Watson, E. (2008). Ranking, rating and scoring of tourism journals: interdisciplinary challenges and innovations. Tourism Management, 29(1), 66-78. Link Jones, P. (1996). Viewpoint. Hospitality-research. Where have we got to? International Journal of Hospitality Management, 15(1), 5-10. Link Kahn, M. & Olsen, M. (1988). An overview of research in Hospitality education. The Cornell Hotel and and Restaurant Administration Quarterly, 29(2), 54-65. Link Keiser, J. (1998). Hospitality and tourism: a rhetorical analysis and conceptual framework for identifying industry meanings. Journal of Hospitality and Touris Research, 22(2), 115-128. Link Kim, Y., Savage, K., Howey, R. & Van Hoof, H. (2009). Academic foundations for hospitality and tourism research: A reexamination of citations. Tourism Management, 30(5), 752-758. Link King, C.A. (1995). Viewpoint. What is hospitality? Internacional Journal of Hospitality Management, 14(3-4), 219-234. Link King, C., Funk, D.C. & Wilkins, H. (2011). Bridging the gap: An examination of the relative alignment of hospitality research and industry priorities. International Journal of Hospitality Management, 30(1), 157-166. Link Korstanje, M. (2009). Turismo: un nuevo enfoque disciplinario para la enseñanza académica. TURyDES - Revista de Investigación en Turismo y Desarrollo Local, 2, 1-21. Link Korstanje, M. (2010). Elemental forms of Hospitality. Revista Brasileira de Pesquisa em Turismo, 4(2), 86-111. Link Korstanje, M. (2016). La transdisciplinariedad en los estudios turísticos. Turismo, Desarrollo y Buen Vivir, Revista de Investigación de la Ciencia Turística-RICIT, 10, 1-15. Link Korstanje, M. (2017). Tourism research, for what? Turismo y Sociedad, 20, 75-86. Link Korstanje, M. & Olsen, D. H. (2011). The discourse of risk in horror movies post 9/11: hospitality and hostility in perspective. International Journal of Tourism Anthropology, 1(3-4), 304-317. Link Korstanje M. & Tarlow, P. (2012). Being lost: tourism, risk and vulnerability in the post-‘9/11’entertainment industry. Journal of Tourism and Cultural Change, 10(1), 22-33. Link Korstanje, M., Mustellier, L. C. & Herrera, S. (2016). Understanding the indiscipline of tourism: A radical critique to the current. Global Dynamics in Travel, Tourism and Hospitality. (pp. 208-217). Hershey: IGI Global, Kotler, P. Bowen, J. & Makens, J. (1997). Mercadotecnia para hotelería y turismo. México: Prentice Hall. Kotler, P., Heider, D.H. & Rein, I. (1993). Marketing places: attracting investment, industry and tourism to cities, states and nations. New York: The Free Press. Law, R. & Chon, K. (2007). Evaluating research performance in Tourism and Hospitality: the perspective of university program heads. Tourism Management, 28(5), 1203-1211. Link Laws, E. (1991). Tourist marketing, service and quality management perspectives. Cheltenham: Stanley Thornes. Laws, E. (1995). Tourist destination management, issues, analysis and policies. London: Routledge. Laws, E. (2000). Service quality in tourism research: are we walking tall (yet)? Journal of Quality Assurance in Hospitality & Tourism, 1(1), 31-56. Link Lugosi, P., Lynch, P. & Morrison, A. (2009). Critical hospitality management research. The Service Industries Journal, 29(10), 1465-1478. Link Mckercher, B., Law, R. & Lam, T. (2006). Rating tourism and hospitality journals. Tourism Management, 27(6), 1235-1252. Link Middleton, V.T.C. (1994). Marketing in travel and tourism. Oxford: Butterworth-Heinemann. Milne, S. & Altejevic, I. (2001). Tourism, economic development and the global-local nexus: theory embracing complexity. Tourism Geographies, 3(4), 369-393. Link Morrison, A. (2002). Hospitality research: a pause for reflection. International Journal of Tourism Research, 4(3), 161-169. Link Morrison, A. & O’Gorman (2008). Hospitality studies and hospitality management: A symbiotic relationship. International Journal of Hospitality Management, 27(2), 214–221. Link Organización Mundial de Turismo - OMT. (1998). Introducción al Turismo. Madrid, OMT. Organización Mundial de Turismo - OMT. (2000). Public-Private Sector Cooperatio. Enhancing Tourism Competitiveness. Madrid: OMT. Organización Mundial de Turismo - OMT (2012). Panorama OMT del Turismo internacional. Madrid: OMT. Organización Mundial de Turismo - OMT (1998). Introducción al Turismo. Madrid: OMT. Ottenbacher, M., Harrington, R. & Parsa, H.G. (2009). Defining the Hospitality Discipline: a discussion of pedagogical and research implications. Journal of Hospitality & Tourism Research, 33(3), 263-283. Link Park, K., Phillips, W.J., Canter, D. & Abbott, J. (2011). Hospitality and Tourism research rankings by author, university, and country using six major journals: the first decade of the new millennium. Journal of Hospitality and Tourism Research, 35(3),381-416. Link Pechlaner, H., Zehrer, A., Matzler, K. & Abfalter, D. A (2004). Ranking of international Tourism and Hospitality Journals. Journal of Travel Research, 42(4), 328-332. Link Pedreño, A. & Monfort. (1996). Introducción a la economía del Turismo en España. Madrid: Cívitas. Penchaszadeh, A. P. (2012). Los desafíos políticos de la hospitalidad: Perspectivas derrideanas. Alteridades, 22(43), 35-45. Link Pigram, J. J. & Wahab, S. (Eds.). (2005). Tourism, development and growth: the challenge of sustainability. Abingdon: Routledge. Racherla, P. & Hu, C. (2010). A social network perspective of Tourism Research collaborations. Annals of Tourism Research, 37(4), 1012-1034. Link Rivera, M. A. Y Upchurch, R. (2008). The role of research in the hospitality industry: a content analysis of the IJHM between 2000 and 2005”. International Journal of Hospitality Management, 27(4), 632-640. Link Roper, A., & Brookes, M. (1999). Theory and reality of interdisciplinary research. International Journal of Contemporary Hospitality Management, 11(4), 174-180. Link Ruiz, A. V., Olarte, R., & Iglesias, V. (1999). Evaluación de los destinos turísticos en función de su valor de marca. Actas… XI Encuentro de Profesores Universitarios de Marketing, 427-450. Link Russell, R. & Faulkner, B. (2004). Entrepreneurship, chaos and the tourism area lifecycle. Annals of Tourism Research, 31(3), 556-579. Link Ryan, C. (1991). Recreational tourism: A social science perspective. London: Routledge. Ryan, C. (2005). The ranking and rating of academics and journals in Tourism Research. Tourism Management, 26(5), 657-662. Link Serrano Larráyoz, F. (2014). Del reino de Pamplona al reino de Navarra: el entramado sanitario (siglos XII-XIII). Journal of Medieval Iberian Studies, 6(2), 192-213. Link Severt, D.E., Tesone, D.V., Bottorff, T.J. & Carpenter, M.L. (2009). A world ranking of the top 100 Hospitality and Tourism Programs. Journal of Hospitality and Tourism Research, 33(4), 451-470. Link Sharpley, R. (2000). The influence of the accommodation sector on tourism development: lessons from Cyprus. International Journal of Hospitality Management, 19(3), 275-29. Link Shaw, M. & Nightingale, M. (1995). Scholarship reconsidered: implications for hospitality education. Hospitality Research Journal, 19(1), 81-93. Link Sheldon, P. J. (1991). An authorship analysis of Tourism Research. Annals of Tourism Research, 18(3), 473-484. Link Silva, J., Rodrigues, P., Mendes, J. & Pereira, L. (2010). A Tourism research agenda for Portugal. International Journal of Tourism Research, 12, 90-101. Link Southern, G. (1999). A systems approach to performance measurement in hospitality. International Journal of Contemporary Hospitality Managemen, 11(7), 366-376. Link Sturman, M. (2003). Building a bridge from the other bank: this issue’s focus on research methods and tools for hospitality management. Cornell Hotel and Restaurant Adminstration Quarterly, 44(2), 9-13. Link Taylor, S. & Edgar, D. (1996). Hospitality research: the emperor’s new clothes? International Journal of Hospitality Management, 15(3), 211-227. Link Travis, A.S. (1989). Tourism destination area development. En S.F. Witt & L. Moutinho. Tourism marketing and management handbook. (pp. 75-95). London: Prentice Hall. Thirkettle, A. & Korstanje, M. E. (2013). Creating a new epistemology for Tourism and Hospitality disciplines. International Journal of Qualitative Research in Services, 1(1), 13-34. Link Tideman, M. C. (1983). External influences on the hospitality industry. The Management of Hospitality., 1-23. Link Timothy, D. & Teye, V. (2009). Tourism and the Lodging Sector. Oxford: Elsevier Tribe, J. (1997). The indiscipline of tourism. Annals of Tourism Research, 24(3), 638-657. Link Van Scotter, J. & Culligan, P.E. (2003). The value of theoretical research and applied research for the hospitality industry. Cornell Hotel and Restaurant Administration Quarterly, 44(2), 14-27. Link Vargas Sánchez, A. (2011). ¿Los principales destinos son también las principales potencias en la investigación en Turismo? Estudios Turísticos, 188, 91-111. Link Wickens, E. (2002). The sacred and the profane: A tourist typology. Annals of Tourism Research, 29(3), 834-851. Link Witt, S.F. & Moutinho, L. (1989). Tourism marketing and management handbook. London: Prentice Hall. Wood, R. (1999). Traditional and alternative research philosophies. In B. Brotherton (Ed.) The handbook of contemporary hospitality management research. (pp: 3-18). Wiley: Chichester. Xiao, H. & Smith, S. L. J. (2006). The making of tourism research: insights from a Social Sciences Journal. Annals of Tourism Research, 33(2), 490-507. Link Xiao, H. & Smith, S. L. J. (2008). Knowledge impact an appraisal of Tourism scholarship. Annals of Tourism Research, 35(1), 62-83. Link Zhao, W. & Ritchie, J. R. B. (2007). An investigation of academic leadership in Tourism Research: 1985-2004. Tourism Management, 28(2), 476-490. Link PROCESSO EDITORIAL Recebido: 22 OUT 18. Avaliado: NOV 18 - MAI 19. Aceito: 7 DEZ 19